Polymer Brushes Supported Polyoxometalate Catalyst for Ultra-Deep Desulfurization of Diesel - Shi, Lei; Wei, Zhong; Zhu, Mingyuan; Yuan, Jun; Dai, Bin (Asian Journal of Chemistry, 2013)
In this paper, a novel catalyst (PMo12O40-PDMAEMA-SiO2) with polymer brushes as support was synthesized in this paper. The catalysts were characterized by thermogravimetric analysis and fourier transform infrared spectroscopy and the results suggested that PDMAEMA was formed on the surface of SiO2 and [PMo12O40]3– existed in the obtained catalyst. PMo12O40-PDMAEMA-SiO2 was further used as oxidative catalyst in desulfurization process of dibenzothiophene dissolved in n-octane. PMo12O40-PDMAEMA-SiO2 was found to be very effective for the oxidative removal of dibenzothiophene with desulfurization efficiency about 100 %. Experimental factors including type of different sulfur-containing compounds, O/S molar ratio, temperature, catalyst amount were evaluated and the optimal operating conditions were determined as O/S molar ratio, 24; reaction temperature, 60 ºC; the amount of catalyst, 0.008 g (5 mL model oil). Moreover, the new catalyst developed is reuseable. The recyclable PMo12O40-PDMAEMA-SiO2 exhibited good catalytic performance and can be recycled for four times without significant decrease in catalytic activity. As a whole, PMo12O40-PDMAEMA-SiO2 has high potential for using as an effective catalyst for deep desulfurization of diesel.